Koreografi â€œPETI = MATIâ€: Otokritik Fenomena Sosial Dompeng di Sarolangun, Jambi - Syaputra, Redho; Rasmida, Rasmida; Martion, Martion (Besaung : Jurnal Seni Desain dan Budaya)
Koroegrafi titled "PETI = Dying" is the result of the interpreter's imagination and imagination in pouring ideas into the form of works about PETI or Dompeng activities. PETI or Dompeng is a mining business that is carried out by individuals, groups of people or companies with legal entities whose operations do not have permits from government agencies in accordance with applicable laws and regulations. Miners are supported by large investors who use heavy equipment to dredge sand and river so that it can quickly cause damage along the watershed. To purify gold, miners use mercury, then dump their waste directly into the river. Disposal of mercury poison is very severe in the upper area of Batang Tembesi. Choreography is arranged based on abstract type supported by setting and music to convey the message and impression of the dance work. The foothold in choreography departs from forms of pure motion, namely the activities of gold miners. To convey the contents of the choreography will be strengthened by seven dancers consisting of six male dancers and one female dancer. With the theme of life, who wants to convey messages and impressions to the audience about the importance of protecting natural resources and environmental preservation. The concept of this work is the result of observations of the workman, especially what happened in his personal life where the workmanship of the workman who was born and delivered in Sarolangun felt his direct impact. To visualize arable ideas into dance works.